Coverage and costs of childhood immunizations in Cameroon - Hugh R. Waters; Leanne Dougherty; Simon-Pierre Tegang; Tran Nhan; Charles Shey Wiysonge; Long Kanya; Nathan D. Wolfe; Donald S. Burke (The World Health Organization, 2004)
OBJECTIVE: To quantify the association between household-level and provider-level determinants and childhood immunization rates in Cameroon while also calculating the cost of childhood immunizations. METHODS: This study uses multilevel regression analysis to calculate these relationships. The 1998 Cameroon Demographic and Health Survey and the 2000 Multiple Indicator Cluster Survey are the main sources of household-level data. These surveys are supplemented by data from a 2002 survey of health facilities conducted in three provinces. At the national level, immunization financing data were collected from the Ministry of Health and donors that support the national Expanded Programme on Immunization. FINDINGS: The 1998 survey found that nationally 37% of children were fully immunized; the 2000 survey found that nationally 34% were fully immunized. These results are strongly correlated with both the mother's level of education and the household's economic status. Multilevel logistic regression shows that maternal education level is a stronger predictor of positive immunization status than is relative economic status. Children of mothers with secondary education or higher education were 3 times more likely to be fully vaccinated than children whose mothers had not completed primary education. At the health-facility level, both having an immunization plan and regular supervisory visits from someone at the health-district level are strongly positively associated with immunization rates. The cost of routine vaccinations for each fully immunized child is US$ 12.73 when donors' contributions are included but not the costs of immunization campaigns. CONCLUSION: Studies conducted in the 1980s and 1990s found that costs per fully immunized child varied from US$ 2.19 to US$ 26.59 (not adjusted for inflation) in a range of low-income and middle-income countries. The relatively low rates of immunization coverage in Cameroon, and the strong influence of the household's socioeconomic status - particularly the mother's level of education - on immunization rates suggest that the effectiveness of the Cameroon programme could be increased by promoting immunization and directing such programmes towards households with limited resources.